Generalisation of the oxide reinforcement model for the high oxidation resistance of some Mg alloys micro-alloyed with Be. (February 2019) - Tan, Qiyang; Mo, Ning; Lin, Chih-Ling; Zhao, Yitian; Yin, Yu; Jiang, Bin; Pan, Fusheng; Atrens, Andrej; Huang, Han; Zhang, Ming-Xing
Graphical abstract: Highlights: Microalloying with Be effectively improved the oxidation resistance of Mg-2Zn, Mg-2Sn, AS21 and ZC63. Microalloying with Be had little effect on the oxidation resistance of ZK20, AM60 and Mg-2Y. The oxidation resistance of Mg alloys was closely related to the mechanical strength of the initially formed oxide layers. The nanoindentation testing provides a new approach to understand the mechanism for the oxidation resistance of Mg alloys. Abstract: The present work studied how Be influences Mg alloy oxidation. Be microalloying significantly decreased the oxidation rate at 500 °C and increased the ignition temperatures of as-cast Mg-2Zn, Mg-2Sn, AS21, and ZC63. However, Be addition had little effect on the oxidation resistance of as-cast ZK20, AM60 and Mg-2Y. Based on the nanoindentation results, the present results can be well understood and explained using the recently proposed oxide layer reinforcement model, which indicates that the mechanical strength of the initially formed oxide controls Mg alloy oxidation.